18. Simultaneous recording of motor related cortical potentials to different basal components of voluntary movements during a sustained fatigue task. Issue 12 (December 2016) - Troni, W.; Boretto, F.; Sapio, A. Di; Melillo, F.; Morese, R.; Valentini, M.C.
Abstract : Our aim was to study the effects of a sustained fatigue task on Motor Related Cortical Potentials (MRCPs) to basic components of voluntary movements. In 10 normal volunteers MRCPs to Ballistic, Extension movements and Relaxation of the right index finger, according to the method described in the companion paper (Troni et al., 1966) were recorded during a sustained (80 min) fatigue task. The task consisted in continuous finger extension to maintain a fixed position at half of maximal range of motion (basal position) while supporting a load (30–50 g) hanging on distal phalanx. The sequence of the 3 motor tasks was superimposed to the fatigue task. Fatigue was monitored using a 10 points Visual Analogic Scale (VAS). A significant increase in amplitude of all post-movement components was observed in Bt- and Ex-MRCPs, associated with a substantial stability of pre-movement components (early- and late-BP) throughout the experimental session. A similar trend was initially observed for Re-MRCP, later followed by a progressive reduction in amplitude of both late-BP and post-movement components. The post-movement changes of Bt- and Ex-MRCP can hardly be attributed to fatigue because of early occurrence and temporal stability. The late and progressive deterioration of Re-MRCP strongly indicates a fatigue effect.